2009 ASHRAE handbook fundamentals. (American Society of Heating, Refrigeration and Air-Conditioning Engineers, 2009)
Annotation The 2009 ASHRAE Handbook"Fundamentals covers basic principles and data used in the HVAC&R industry. Updated with research sponsored by ASHRAE and others, this volume includes 1,000 pages and 39 chapters covering general engineering information, basic materials, climate data, load and energy calculations, duct and pipe design, and sustainability, plus reference tables for abbreviations and symbols, I-P to SI conversions, and physical properties of materials. An accompanying CD-ROM (free with the book"also sold separately) contains all the volume's chapters in both I-P and SI units.
Keywords: Heating -- Handbooks, manuals, etc.; Refrigeration and refrigerating machinery -- Handbooks, manuals, etc.; Air conditioning -- Handbooks, manuals, etc.; Ventilation -- Handbooks, manuals, etc.; elektronické knihy; electronic books